2016
DOI: 10.1177/1557988316664074
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Patients Have Lower Levels of Adropin When Compared With Healthy Overweight/Obese and Lean Subjects

Abstract: Metabolic syndrome (MetS), a cluster of cardiometabolic risk factors, is a challenging public health issue. The aim of current study was to test the hypothesis that concentrations of plasma adropin and leptin differ between patients with MetS and comparable age-and sex-matched control groups. This case-control study involved 153 subjects (51 per group). The study group included obese subjects with MetS and the two control groups included weightmatched subjects without MetS ("healthy": obese) and normal weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…When we considered components of MetS, we observed that adherence to a diet with high inflammatory potential was positively associated with reduced levels of HDL-C. No other significant association was observed between DII and other components of MetS. Similar to our findings, a cross-sectional study conducted by Yosaee et al, indicated that higher scores of DII were associated with greater odds for having reduced concentrations of HDL-C. 5 In another study, Pimenta et al reported an inverse association between the inflammatory potential of diet and serum levels of HDL-C. 18 In opposite with our results, Naja et al found no significant association between DII and serum levels of HDL. 32 Such non-significant association was also reported in two other studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When we considered components of MetS, we observed that adherence to a diet with high inflammatory potential was positively associated with reduced levels of HDL-C. No other significant association was observed between DII and other components of MetS. Similar to our findings, a cross-sectional study conducted by Yosaee et al, indicated that higher scores of DII were associated with greater odds for having reduced concentrations of HDL-C. 5 In another study, Pimenta et al reported an inverse association between the inflammatory potential of diet and serum levels of HDL-C. 18 In opposite with our results, Naja et al found no significant association between DII and serum levels of HDL. 32 Such non-significant association was also reported in two other studies.…”
Section: Discussionsupporting
confidence: 89%
“…32 Such non-significant association was also reported in two other studies. 5,33 This discrepancy might be explained by different confounders which were adjusted in previous studies. For instance, in the study of Naja et al that found no significant association between DII and HDL concentrations, BMI as an important confounder was not controlled, 32 but in our study, we adjusted for BMI and found a significant positive association between DII and reduced levels of HDL.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, in mice with high-fat diet-induced obesity, serum adropin levels are low (<1 ng/mL). An inverse correlation of adropin levels and body mass index (BMI) was also confirmed by human studies [4,[12][13][14][15][16][17]], suggesting that a low level of adropin is a hallmark of obesity. Nevertheless, a recent detailed study showed that this association should be interpreted cautiously.…”
Section: Modulation Of Adropin By Body Mass Index (Bmi) Diet and DImentioning
confidence: 77%
“…Zhang et al (50) found IR index is a negative independent risk factor of ADR levels in obese adolescents. Yosaee et al (51) reported that subjects with metabolic syndrome had significantly lower ADR levels and adropin/leptin ratio and ADR levels were correlated with metabolic syndrome and hence is a potentially protective agent against its development. (47) considered the high ADR levels as one of the multiple adaptive responses on adverse glucose metabolism during pregnancy; however, Hill (52) documented that as gestation progresses several parallel mechanisms contribute to increasing maternal β-cell mass through reactivation of β-cell proliferation and an expansion and differentiation of resident β-cell progenitors and these pathways could potentially be modulated during pregnancy to increase β-cell mass and prevent the onset of GDM.…”
Section: Discussion:-mentioning
confidence: 99%